2021
DOI: 10.5194/hess-2021-89
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Missing connectivity during summer drought controls DOC mobilization and export in a small, forested catchment

Abstract: Abstract. Understanding the controls on event-driven DOC export is crucial, as DOC is an important link between the terrestrial and the aquatic carbon cycles. We hypothesize that topography is a key driver of DOC export because it influences hydrologic connectivity, which can inhibit or facilitate DOC mobilization. To test this we studied the mechanisms controlling DOC mobilization and export in the Große Ohe catchment, a forested headwater in a mid-elevation mountainous region in Southeastern Germany. Dischar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 80 publications
2
10
0
Order By: Relevance
“…Rainfall and snowmelt events also occurred during the study period. Their effect on DOC mobilization is discussed in a separate paper by Blaurock et al (2021).…”
Section: Dischargementioning
confidence: 99%
See 1 more Smart Citation
“…Rainfall and snowmelt events also occurred during the study period. Their effect on DOC mobilization is discussed in a separate paper by Blaurock et al (2021).…”
Section: Dischargementioning
confidence: 99%
“…The objective of this study is to characterize the spatial changes in DOC concentration and DOM composition along a low‐order stream in a temperate, mountainous forested catchment in southern Germany with a focus on baseflow conditions. Previous work has shown that DOC export during rain events reflects varying contribution of different parts of the catchment (upper and lower) triggered by antecedent hydrological conditions and hydrological connectivity (Blaurock et al., 2021). Due to the strong gradient in catchment properties between upper and lower part (mean slope, proportion of hydromorphic soils, see below), we hypothesize that also during baseflow, the DOM composition in the steep (upper) part of the catchment is mainly driven by groundwater input, while in the flat (lower) part, also varying contribution from riparian topsoil shape the DOM composition in the stream.…”
Section: Introductionmentioning
confidence: 99%
“…Each event included all days classified as storm flow for the corresponding time period, plus the day classified as base flow prior the days classified as storm flow, which was considered as the starting date of the event. This strategy followed Blaurock et al (2021) and ensured that the relevant magnitude and range of the associated hydroclimatic event https://doi.org/10.5194/hess-2021-401 Preprint. Discussion started: 12 August 2021 c Author(s) 2021.…”
Section: Hydroclimatic Analysis Of Large Storm Eventsmentioning
confidence: 99%
“…Precipitation activates direct wet deposition and indirect dry deposition deriving from vegetation canopy and stem (Song et al, 2021) and soil erosion (Chaplot and Mutema, 2021). This contribution to total DOC export is further emphasized if the wet event occurs at the end of prolonged dry periods (Blaurock et al, 2021). Fazekas et al (2020) highlighted that anomalous events lasting overall less than 20 days in a year could define the annual behaviour of the relationships between streamflow and organic matter concentration.…”
Section: Introductionmentioning
confidence: 99%
“…Within the same catchment, significant differences can arise, which cannot be fully captured by a single downstream monitoring section that integrates heterogeneous upstream biogeochemical signals. It is a typical problem of scale (Lowe et al, 2006;McGuire et al, 2014), which also affects streamwater chemistry and needs to be addressed with innovative theoretical concepts and technical approaches, including intensive spatially distributed monitoring campaigns in nested sections of the same catchment (McGuire et al, 2014;Blaurock et al, 2021). DOC dynamics monitoring across different spatial and temporal scales is possible thanks to the advancements in optical aquatic sensors technology.…”
Section: Introductionmentioning
confidence: 99%